Decoding: A Guide to Kodak Paper Surface Characteristics. Issue 2 (June 2018) - Fisher, Erin
From 1880 to 2005, the Eastman Kodak Company manufactured black-and-white fiber-based gelatin silver paper in a wide variety of weights, grades, and formats. Kodak manufacturer records and sample books include details about Kodak paper surface characteristics and are an invaluable resource for understanding photographic paper materials. Using the extensive number of Kodak data books, manuals, and manufacturing records spread out in the collections of three Rochester, New York-based institutions—George Eastman Museum, University of Rochester Special Collections, and Image Permanence Institute—I created a chronological guide to Kodak photographic paper surface characteristics. This guide is not an approximate identification guide for Kodak papers but rather a resource that can be used to fill in gaps and propose questions about Kodak manufacturing history that is no longer easily accessible. The guide aims to help researchers, photography archivists and historians, conservators, collection managers, or anyone else interested in Kodak history gain access to a better understanding of photographic paper produced by Kodak from 1930 to 1955. The process for creating the guide is described in this article and may be used as a starting point for future research while also illuminating the importance of documenting and providing access to technological and material details about photographic objects.